Analyse Diagnostique De L’élevage Des Canards De Race Locale (Cairina Moschata Linnaeus, 1758) Dans Le Sud Forestier De La Côte d’Ivoire - Amanidja Boye Donatien; Komara Moussa; Soro Dofara; Loba Akou Logboh Emma Gladys; Atcho Otchoumou (European Scientific Journal, ESJ, 2018)
The duck is one of the indigenous poultry species in Ivory Coast that production is in rudimentary stage. This present study was conducted to identify the systems of breeding, to characterize the number of animal, management practices and the mortality of local ducks through a survey. The survey has been made in participative form of the 375 local duck breeders from the communes of Abobo, Bassam, Bingerville, Port-Bouёt and Songon. The survey showed two (02) systems of breeding: an extensive family system with ducks in divagation (88,62%) and an extensive family system of farmyard with ducks in captivity with (11,38%). The higher breeders (48,26 %) possesses minus or ten local duck in their flock. Local duck breeders provided a shelter of night (98%). The factors that decimate the local duck has been domestic accident (27,75 %), erosion (34 %) and the predatory (20,5%) in the south forest from Ivory Coast. Mortalities has been higher in the females (30,10%) than males (14,98%). However, duckling (62,5%) dead more than the young duck (20,25%) or the adults duck (10,25%). In conclusion, the local duck breeding is confronted to many constraints, but the installation of rational system of management could help the breeders to improve to increase the productivity of these poultries.